Detection of Helicobacter pylori genes (CagA and VacA) in municipal drinking water - Fathollah Gholami-Borujeni; Hamzeh Rahimi; Seyed Mehdi Sajjadi (Environmental Health Engineering and Management, 2022)
Background: Helicobacter pylori is classified as a carcinogen, and it is also the most common cause of chronic bacterial infection and peptic ulcers. Approximately 45% of people are infected with the bacterium. Methods: In this study, the H. pylori genes, CagA and VacA, were investigated in drinking water, using 100 samples (50 samples from the municipal water supply and 50 samples from the effluent of household water treatment devices). DNA was extracted from colonies with a positive heterotrophic plate count (HPC) for use in molecular testing and microbial identification. The polymerase chain reaction (PCR) was used to identify H. pylori. Results: The study showed that 24% of urban water samples (12% above the World Health Organization [WHO] standards for safe drinking water) and 18% of home water treatment-device samples (4% above the WHO standards) were HPC-positive. The H. pylori genes, CagA and VacA, were identified in 2% of the samples from household water treatment devices and 8% of the municipal water supply samples. Conclusion: The study findings show that H. pylori may be transmitted in drinking water. However, there is currently no strong evidence that the bacteria can survive after the disinfection process in the water supply system. Therefore, the health risks of this bacterium in drinking water are still unknown.